Microzonation Study on the Western Area of Napoli. (2016) - Licata, Valeria; Forte, Giovanni; d'Onofrio, Anna; Evangelista, Lorenza; Jalayer, Fatemeh; Santo, Antonio; Silvestri, Francesco
Abstract: A rational evaluation of the seismic risk of urban areas cannot neglect the variability of the ground motion due to site amplification and the induced effects, such as soil liquefaction and slope stability. In this framework, the microzonation maps certainly represent the most adequate tool to account for this element in the seismic risk and for planning mitigation strategies. This study shows the preliminary results of a multidisciplinary research, which deals with the seismic microzonation of the Western area of Napoli. The selected case study is a challenging choice, as the seismic hazard is affected by both tectonic and volcanic seismicity, which in historical time differently affected the urban setting. The latter, in turn, results highly heterogeneous, as consisting of a mixing of both masonry and concrete structures. The adopted approach followed the recommendations of both the National and International Guidelines, with reference to the multi-levels methods. The collection, homogenization and synthesis of a significant number of existing data permitted the development of reliable geological and geotechnical subsoil models, leading to Grade I and II seismic microzonation maps, characterized by different expected amplification of ground motion and instability due to the liquefaction. Such maps represent a key for a quantitative assessment of seismic performance of buildings and infrastructures, in view of the expected urban requalification of the area.